MANAJEMEN PENGEMBANGAN LEMBAGA PENDIDIKAN ISLAM QURANI DI MTs. AT TAQWA BONDOWOSO - Saharani, Lepisa (As-Sulthan Journal of Education, 2024)
This study examines the management of the development of Quranic value-based educational institutions at Islamic Junior High Shool of  At Taqwa Bondowoso which focuses on aspects of planning, organizing, implementing, and monitoring and evaluating. This research is a type of field research, using a qualitative approach to explore the implementation strategy of Quranic values in madrasah development. Data were obtained through in-depth interviews, participatory observation, and document analysis, with triangulation techniques to increase validity. The collected data were systematically analyzed using interactive analysis through data reduction, data presentation, and conclusion drawing. Research findings, the concept of Quranic development at Islamic Junior High Shool of At Taqwa Bondowoso uses the concept of Tilawah, Tadzkiya, Ta'lim (3T), where Islamic Junior High Shool of  At Taqwa integrates the concept in the management aspect and focuses on several areas of development, namely curriculum, human resources, infrastructure, student culture, and educational technology. The conclusion of the research is that the concept of madrasah development can be used as a model for the development of Islamic educational institutions that are relevant to modern needs, while remaining steadfast to the values of the Quran as the basis of education.